Risk factors for oropharyngeal dysphagia in cardiovascular diseases - de ALMEIDA, Tatiana Magalhães (2020)
Some conditions consolidated as risk factors for oropharyngeal dysphagia have already been identified in other diseases, such as neurological. Studies on cardiovascular diseases concentrate in individuals in the postoperative period; thus, it is unknown if these same factors occur in individuals hospitalized for clinical or surgical treatment of these diseases. Objective: to correlate predictive risk factors for oropharyngeal dysphagia in individuals with cardiovascular disease admitted at a reference cardiology hospital. Methodology: This is a retrospective clinical study. Medical records of 175 individuals hospitalized for clinical and/or surgical treatment at a reference cardiology hospital from January to June 2017, attendants of the Speech-Language Pathology and Nutrition team, were analyzed. Of these, 100 records were included in the study: 41 females and 59 males (mean age 67.56 years). Deaths and individuals from 0 to 18 years were excluded. Stroke, malnutrition, age and prolonged orotracheal intubation were considered predictive risk factors for oropharyngeal dysphagia. Mann-Whitney test and Fisher's test were used for statistical analysis. Results: Stroke (OR=2.93 p=0.02), malnutrition (OR=2.89 p=0.02) and prolonged orotracheal intubation (OR=3.94 p=0.02) were statistically significant predictors for oropharyngeal dysphagia within this population. Age below 80 years was not significant (p=0.06), but within octogenarians, significance was found (p=0.033). Conclusion: Stroke, malnutrition, prolonged orotracheal intubation and age > 80 years are predictive risk factors for oropharyngeal dysphagia in adult population with cardiovascular diseases.